Religious Understanding among Foster Children through Social and Spiritual Guidance Programs at the Aisyiyah Orphanage, Matur, West Sumatra - Nurdeli Indah Sari (UIN Sjech M. Djamil Djambek Bukittinggi, 2025)
This research is motivated by the need to understand the level of religious understanding among foster children in carrying out social and spiritual guidance activities, as reflected in their behavior and their ability to comprehend and apply what they learn. Education is not only acquired through formal institutions but also through informal settings, such as activities conducted in orphanages, which serve as compulsory supplementary educational programs for foster children. This study aims to analyze the religious understanding developed through social and spiritual guidance activities at the Aisyiyah Matur Branch Orphanage. This research employs a descriptive qualitative approach. The informants consist of foster children, caregivers, and administrators within the orphanage environment. Data were collected through observation, interviews, and documentation. The theoretical framework used in this study is Talcott Parsons’ structural functionalism theory, particularly the AGIL (Adaptation, Goal Attainment, Integration, and Latency) scheme. The findings indicate that the level of religious understanding among foster children varies. Some foster children demonstrate a low level of religious understanding in participating in social and spiritual guidance activities, as evidenced by behaviors such as joking with peers, sleeping during activities, or not participating at all. These conditions are influenced by factors such as busy schedules, boredom, and less engaging learning methods. However, other foster children are able to internalize and apply the religious values they learn, enabling them to demonstrate positive behavior and compete with children outside the orphanage environment.